A dynamic heuristic for WSNs routing. Issue 1 (1st January 2021) - Tounsi, Mohamed
Abstract: One of the most important issues in the wireless sensor networks (WSNs) is nodes energy. The routing protocols as well as nodes management are considered as the key elements to improve a network's lifetime. In this research, we have suggested a dynamic heuristic for new nodes selection that manages efficiently the active nodes using a Tabu Node Selection coupled with minimum spanning tree routing protocol (TNS). Minimizing the total energy consumption in WSN, is not enough alone, since some nodes drain their energy faster than others, and may cause network failure. To balance the energy consumption, our strategy is to identify nodes with high-energy depletion and balance data routing on their neighbours. This approach performs nodes energy balancing, by creating lists of Tabu nodes (periodically inactive nodes). Such a scheme will prevent the most used nodes, such as nodes close to the base station to see their energy drain. The nodes in the Tabu lists will dynamically be active according to the energy level of nodes surrounding them. Our new dynamic heuristic has proven to outperform other nodes management approach which does not use Tabu search. The experiments show that Tabu list combined with Minimum Spanning Tree routing protocol extend drastically the network lifetime by balancing optimally the nodes energy.